Clinical Profile of Dengue Fever and Dengue Haemorrhagic Fever in Children during an Outbreak in Timor Leste, 2005 - Rimal, Hem; Espejo, Daisy Joy; Reyes, Jocelyn; Sarmento, Angelo Da Silva; Mango, Ana; Santos, Milena Maria LayDos (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 44-49 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8804